2004
DOI: 10.1124/dmd.32.4.455
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Residue Ile211 Is Essential for the Enzymatic Activity of Human Udp-Glucuronosyltransferase 1a10 (Ugt1a10)

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Conjugation of exogenous and endogenous compounds by uridine diphosphoglucuronosyltransferases (UGTs) is a pathway catalyzing the transfer of a glucuronic acid molecule from UDP glucuronic acid to lipophilic aglycones, which become more polar and more easily excretable in the bile or urine. UGTs are divided into two major families, UGT1 and UGT2. The isoform UGT1A10, along with UGT1A7 and UGT1A8, is expressed exclusively in extrahepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The latter observation and the loss of 4MU and 1NP glucuronidation activity associated with the UGT1A and UGT2B7 His3 Pro mutations are consistent with the hypothesis that the N-terminal domain histidine generally, but not invariably (Kubota et al, 2007;, acts as the catalytic base in the metabolism of compounds requiring proton abstraction for glucuronide formation. Taken together with previous reports (Dubois et al, 1999;Senay et al, 2002;Martineau et al, 2004;Xiong et al, 2006;Barre et al, 2007;Kubota et al, 2007;, the present study further demonstrates the pivotal roles of individual amino acids in determining the substrate selectivities of human UGT enzymes.…”
Section: Influence Of Pro and His Residues On Ugt Activitysupporting
confidence: 62%
See 1 more Smart Citation
“…The latter observation and the loss of 4MU and 1NP glucuronidation activity associated with the UGT1A and UGT2B7 His3 Pro mutations are consistent with the hypothesis that the N-terminal domain histidine generally, but not invariably (Kubota et al, 2007;, acts as the catalytic base in the metabolism of compounds requiring proton abstraction for glucuronide formation. Taken together with previous reports (Dubois et al, 1999;Senay et al, 2002;Martineau et al, 2004;Xiong et al, 2006;Barre et al, 2007;Kubota et al, 2007;, the present study further demonstrates the pivotal roles of individual amino acids in determining the substrate selectivities of human UGT enzymes.…”
Section: Influence Of Pro and His Residues On Ugt Activitysupporting
confidence: 62%
“…All UGT1A enzymes contain an identical carboxyl terminus of 246 residues but unique N-terminal domains (residues 1 to 285-289) , indicating that the latter region must determine substrate selectivity. Studies with chimeric UGT2B proteins have similarly associated the N-terminal domain with the substrate selectivities of several human, rabbit, and rat UGT2B enzymes (Mackenzie, 1990;Ritter et al, 1992Ritter et al, , 1993Li et al, 1997;Lewis et al, 2007), whereas site-directed mutagenesis has identified specific N-terminal domain residues involved in the binding of substrates of human UGT1A3, 1A4, 1A6, 1A10, 2B4, 2B15, and 2B17 (Dubois et al, 1999;Senay et al, 2002;Martineau et al, 2004;Xiong et al, 2006;Barre et al, 2007;Kubota et al, 2007;.…”
mentioning
confidence: 99%
“…The broad tissue distribution and substrate specificity of UGT1A10 indicate that it may contribute to the extrahepatic detoxification of endogenous and xenobiotic compounds, especially orally administered drugs such as warfarin, and our past and current studies show that it is also involved in the glucuronidation of hydroxywarfarins Zielinska et al, 2008). Although there are many studies focused on the substrate specificity of UGT1A10, studies attempting to identify catalytically important amino acids and the characteristics of the binding site are less prevalent (Martineau et al, 2004;Basu et al, 2005;Xiong et al, 2006Xiong et al, , 2008Starlard-Davenport et al, 2007;Miller et al, 2008).…”
Section: R- S-hydroxywarfarin Glucuronidation 53mentioning
confidence: 99%
“…3B). We also cite studies by other investigators who analyzed radiolabeled glucuronides following similar TLC resolution (Mackenzie, 2000;Martineau et al, 2004).…”
Section: :768-773 (2004)mentioning
confidence: 99%
“…3B). We also cite studies by other investigators who analyzed radiolabeled glucuronides following similar TLC resolution (Mackenzie, 2000;Martineau et al, 2004).Why carry out differential pH measurements on UGT isozymes? Our aim was to conduct a biochemical study of the individual isozymes using optimal in vitro conditions.…”
mentioning
confidence: 99%